Incidencia de la disortografía en los trastornos de la lecto-escritura de los estudiantes de quinto año de educación básica de la Escuela Honorato Vasquez del Cantón Mocache Provincia de Los Ríos - Gamarra Gonzales, Gabriel Leonardo (2020)
The research work measures the levels of dysgraphia in reading writing in the fifth year students of basic education of the “Honorato Vásquez” school of Mocache canton. The study is of simple descriptive design with quantitative approximation. The sample consisted of 3 students to whom an observation sheet was applied to measure their level of dysgraphia. This research was carried out on the basis of a study of disortography and the proposal of this project is to apply recreational strategies with the purpose of helping to improve the learning of literacy in students, through the use of the practice of reading, writing and spelling rules. These orthographic rules have an exhaustive character in their learning, so they present a series of confusions in the students within their writing; presenting with problems of compression and interpretation of the letters that have similar phonetic configurations, weakening at that time its teaching-learning process. We will make a written test which will allow. Detect this difficulty in order to guide the student correctly clearly. This test will be carried out through practical activities that will serve to correct the disortography since it is the set of writing errors that affect the word and not its path. Thus, when talking about it, the problem is left out. The purpose of this research project is very important because through it we will create competitive students